Epidemiology and population-based incidence of influenza in two communities, Bandung district, West Java, Indonesia, 2008–2011 - Agustian, Dwi; Mutyara, Kuswandewi; Murad, Chrysanti; M. Uyeki, Timothy; B. Kartasasmita, Cissy; Simoes, Eric AF. (Narra Sains Indonesia, 2024)
Influenza surveillance is important for monitoring influenza virus circulation and disease burden to inform influenza prevention and control measures. The aim of this study was to describe the epidemiology and to estimate the incidence of influenza in two communities in West Java, Indonesia, before and after the 2009 H1N1 pandemic. A population-based surveillance study in the community health care setting was conducted to estimate the annual incidence of influenza. A real-time reverse transcription polymerase chain reaction (RT-PCR) assay was used for influenza case ascertainment. A population census was implemented to calculate the population at risk and estimate community health care utilization rate. The mean annual incidence of influenza A and B, adjusted for healthcare utilization, was 1.6 (95%CI: 1.3–2.0) and 0.7 (95%CI: 0.5–1.0) per 1000 persons, respectively, with the most affected group being young and school-age children. The annual cumulative incidence of influenza A for children under five in 2009, 2010, and 2011 was 7.0 (95%CI: 4.4–11.2), 10.6 (95%CI: 7.3–15.4), and 6.3 (95%CI: 3.8–10.2). For influenza B was 4.3 (95%CI: 2.4–7.8), 2.0 (95%CI: 0.8–4.7), and 0.4 (95%CI: 0.1–2.8), respectively. This study highlights that the incidence of influenza among young and school-age children is consistently higher compared to adults and the elderly throughout these periods. These populations are potential targets for influenza vaccination in Indonesia.